Trimerisation of carbon suboxide at a di-titanium centre to form a pyrone ring system - Tsoureas, Nikolaos; Green, Jennifer C.; Cloke, F. Geoffrey N.; Puschmann, Horst; Roe, S. Mark; Tizzard, Graham (Chemical Science, 2018)
The reaction of the syn-bimetallic bis(pentalene)dititanium complex Ti2(μ:η5,η5-Pn†)2 (Pn† = C8H4(1,4-SiiPr3)2) 1 with carbon suboxide (OCCCO, C3O2) results in trimerisation of the latter and formation of the structurally characterised complex [{Ti2(μ:η5,η5-Pn†)2}{μ-C9O6}]. The trimeric bridging C9O6 unit in the latter contains a 4-pyrone core, a key feature of both the hexamer and octamer of carbon suboxide which are formed in the body from trace amounts of C3O2 and are, for example, potent inhibitors of Na+/K+-ATP-ase. The mechanism of this reaction has been studied in detail by DFT computational studies, which also suggest that the reaction proceeds via the initial formation of a mono-adduct of 1 with C3O2. Indeed, the carefully controlled reaction of 1 with C3O2 affords [Ti2(μ:η5,η5-Pn†)2 (η2-C3O2)], as the first structurally authenticated complex of carbon suboxide.